Books and Media (Dartmouth Digital Commons, 2021)
Maia Rauschenberg writes a tribute to Canadian artist Emily Carr in an essay about three books: The Art of Emily Carr by Doris Shadbolt, Growing Pains: the Autobiography of Emily Carr by Emily Carr, and The Forest Lover: A Novel by Susan Vreeland. Reviews of: Desperate Steps: Life, Death and Choices Made in the Mountains of the Northeast by Peter W. Kick. The Lost Art of Reading Nature’s Signs by Tristan Gooley. The Airman’s Arctic Survival Guide by Belmore Browne. 59 Illustrated National Parks by Joel Anderson and Nathan Anderson. Art of Katahdin by David Little.